Risk factors leading to increased rehospitalization rates among adolescents admitted to an acute care child and adolescent psychiatric hospital. Issue 2 (18th September 2017) - McCarthy, Logan; Pullen, Lisa M.; Savage, Jennifer; Cayce, Jonathan
Abstract: Problem: Suicide is the third leading cause of death in adolescents in the United States, with suicidal behavior peaking in adolescence. Suicidal and self‐harming behavior is often chronic, with an estimated 15–30% of adolescents who attempt suicide having a second suicide attempt within a year. The focus of acute psychiatric hospitalization is on stabilization of these psychiatric symptoms resulting at times in premature discharge. Finding from studies based on high rehospitalization rates among adolescents admitted to an acute psychiatric hospital indicates that adolescents continue to experience crisis upon discharge from an acute psychiatric hospital, leading to the question of whether or not these adolescents are being discharged prematurely. Methods: A chart review was performed on 98 adolescent clients admitted to an acute psychiatric hospital to identify risk factors that may increase rehospitalization among adolescents admitted to an acute psychiatric hospital. Clients admitted to the hospital within a 12‐month time frame were compared to clients who were not readmitted during that 12‐month period. Results: History of self‐harming behavior and length of stay greater than 5 days were found to be risk factors for rehospitalization. Conclusions: Adolescent clients who are admitted to an acute psychiatric hospital with a history of self‐harming behavior and extended length of stay need to be identified and individualized treatment plans implemented for preventing repeat hospitalizations.